Sensory evaluation of dairy supplements enriched with reduced iron, ferrous sulfate or ferrous fumarate - Josefina C Morales; Elena Sánchez-Vargas; Rodrigo García-Zepeda; Salvador Villalpando (Instituto Nacional de Salud Pública, 2015)
Objective. To determine the degree of liking of the Oportunidades programme dietary supplements (DS) -purees and beverages- added with different iron salts (IS): reduced iron (RI), ferrous sulphate (FS) or ferrous fumarate (FF) during 24 weeks of storage. Materials and methods. The DS were evaluated through a hedonic scale for aroma, flavour and colour attributes; at time zero and every eight weeks, each panel member evaluated three DS with same flavour and presentation but different IS. Seventy women participated as panel members. Results. The chocolate and banana DS exhibited a change in preference by colour and flavour due to storage. DS with FS or RI showed the least preference by flavour and colour in the context of the three IS considered. The chocolate and neutral DS enriched with FS changed their colour and flavour. Conclusion. DS were, in general, well-liked; nonetheless, for purees enriched with FS and for beverages enriched with RI, the less-liked attributes were colour and flavour